Study on physicals, chemicals and ionic conductivity properties of Polyethylene Oxide (PEO) incorporated with different salts / Siti Nor Ijan Samsudin - Samsudin, Siti Nor Ijan (Faculty of Applied Sciences, 2009)
An investigation on physicals, chemicals and ionic conductivity properties of Polyethylene Oxide (PEO) incorporated with different salts (sodium, magnesium and aluminium salt) in 9:1 ratio revealed the enhancing in physical, chemical and ionic conductivity properties on the polymeric electrolytes. This project shows that the addition of salts to the conducting polymer has decrease the crystallinity of polymer and Mg²⁺ and Al³⁺ can enhance the conductivity and thermal stability of the polymer composite electrolytes.